Rimes de malandrins : du narcocorrido au narco rap - Enrique Flores (Les Cahiers de Framespa)
After the narcocorrido, the narco-rap. The former genealogy of popular ballads and of the printed sheets of bandits and smugglers is founded on the culture of the hip-hop –heaps, rhythm, street language, graffiti and urban inscriptions, dance, body in a transe, visceral politics. “What else?”: artistic and criminal performance; reality as the kingdom of insane violence; Dante’s hell and Rimbaud’s “time of assassins”; jails, drug and misery; Pancho Villa’s mural; Caballeros águila and body painting; outlaw culture and “warriors of the drug” –from the Brazilian jails to the neighborhoods of Los Angeles; “Reynosa la maldosa”; Marcola, Tiger and Subway 3; “Big Word” and “Murderers Artists”; Gangsta rap; narcopoetry and hallucination; poetics of the crime; “Crime pays: rhyme pays”.